The accreditation in the quality of the educational service of the Higher Public Technological Educational Institution "Víctor Raúl Haya de la Torre" Barranca. Region - Lima 2013 - Palacios Olivera, Sandro Percy (2020)
La investigación científica que hemos realizado es básica, correlacional no experimental, los factores de estudio son dos: la acreditación y la calidad del servicio educativo. The population was made up of 30 teachers, 7 Administrative Personnel and 168 ISTP students: “Víctor Raúl Haya de la Torre” of Barranca and the sample is 30 teachers, 7 administrative personnel and 151 students respectively. The research design is translational, correlational, causal. bivariate, transversal. For the data collection, five structured questionnaires were prepared as measurements and refer to the following aspects: teacher's opinion on the principal, teacher's opinion on the quality of the educational service, student's opinion on the director, student's opinion on quality of the educational service and opinion of the administrative staff on the quality of the educational service Four variables are considered in the accreditation variable: strategic management of the principal, teacher performance, institutional support, student opinion and opinion of the administrative staff. Regarding the variable quality of educational service, two dimensions are considered: service satisfaction and service efficiency According to the statistical results obtained, accreditation is related to the quality of the educational service through Rho de Spearman, the level of significance being 95% lower than 0.05, with a correlation of 0.748 which is GOOD. Therefore, the null hypothesis is rejected and the alternative hypothesis is accepted, as follows: The accreditation is related to the quality of the educational service of the I.E.S.T.P “Víctor Raúl Haya de la Torre” of Barranca Region Lima Provinces - Year 2013.